Nancy Richardson for School Board Headquarters on N. Wishon Avenue - Watkins, Howard K. (1975)
Nancy Richardson, Peter Oswald (green jacket), Lois Ehrenberg (white sweater), Mary Louise Frampton, Mario Olmos